Розвиток транспортних мереж пакетної передачі даних - Ведмедеря, М. А. (ХНУРЕ, 2019)
In a hierarchical telecommunications network the backhaul portion of the network comprises the intermediate links between the core network, or backbone network, and the small subnetworks at the edge of the network. In contracts pertaining to such networks, backhaul is the obligation to carry packets to and from that backbone network. A business definition of backhaul is the commercial wholesale bandwidth provider who offers quality of service (QOS) guarantees.